A great leap? Domestic market growth and local state support in the upgrading of China's LED lighting industry - Tobias Ten Brink; Florian Butollo (Global Networks, 2018)
In this article we analyse the conditions for industrial upgrading in the Chinese LED industry, which proactive local state policies and expanding domestic markets have greatly facilitated. State initiatives provoked overinvestment, but eventually led to the emergence of competitive domestic enterprises. Simultaneously, firms benefited from a growing domestic market on which they outcompeted foreign companies in mid-price segments. The combination of these factors accounts for the peculiarly Chinese upgrading experience. Neither the resources provided by a new version of the `developmental state' nor domestic market growth alone can explain the Chinese players' success. Based on these results, and given that the emerging economies have become the most important markets for certain consumer goods – a development that (local) industrial policies for industrial upgrading can influence – we provide further proof that it is necessary to rethink the export-led upgrading paradigm in theories of globally dispersed production.
Keywords: 330; China; global commodity chains; global production networks; global value chains